2014
DOI: 10.1007/s00477-014-0976-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heat and cold waves on circulatory-cause and respiratory-cause mortality in Spain: 1975–2008

Abstract: Few studies have analysed the impact of heat and cold waves on mortality in a given population over the same time period and still fewer studies have analysed this impact in terms of cause-specific mortality. This study analysed the impact of both heat and cold waves on daily all-cause, circulatory-cause and respiratory-cause mortality in the region of Castile-La Mancha (CLM) 1975-2008. The dependent variable was daily all-, circulatory-and respiratory-cause mortality registered in CLM from 01-01-75 to 31-12-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Moreover, it is essential to extend these types of studies to the behaviour over time of cold waves, whose impact on mortality is-at the very leastsimilar to that of heat waves (Linares et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is essential to extend these types of studies to the behaviour over time of cold waves, whose impact on mortality is-at the very leastsimilar to that of heat waves (Linares et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…In Central and Eastern Europe more than 800 deaths caused by hypothermia resulted after extremely cold conditions in the winter of 2011/2012 (Lhotka and Kyselý, ). The effect of CWs on mortality revealed an increase by 12.9% in Spain (Linares et al, ), 10% in China and Russia (Revich and Shaposhnikov, ; Ryti et al, ), and 2.1% in the United States of America (Wang et al, ). Such substantial differences in the excess mortality during HWs and CWs around the world could be explained by the climate, adaptation, and socioeconomic status of each region in which it was reported (Wang et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…HWs cause more deaths all over the world than any other natural hazards (Unkaševic and Tošic, ; D'Ippoliti et al, ; Peterson et al ., ; Shaposhnikov et al, ; Liu et al, ; Nairn and Fawcett, ; Kim et al, ; Chen et al, ). Some previous studies showed an increase in the number of deaths during HWs: between 3.0 and 7.8% in the United States of America (Medina‐Ramón and Schwartz, ; Anderson and Bell, ; Peng et al, ), 21.8% in the Mediterranean areas (D'Ippoliti et al, ), 16.5% in Spain (Linares et al, ), 5% in China (Ma et al, ). At present, it is considered highly likely that anthropogenic effect on climate will double the risk of HWs of the same magnitude of that which occurred in Europe in 2003 and was characterized by a severe impact on population (Montero et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the increase in winter mortality associated with low temperatures has been studied for a number of decades (Mackenbach et al 1992;Kunst et al 1993;Alberdi et al 1998) and has more recently been associated with extremely low temperatures or cold waves Díaz et al 2005;Donaldson and Rintamäki 2001;The Eurowinter Group 1997), it is nevertheless a phenomenon that has attracted far less attention than has the analysis of heat waves, though its impact on mortality is at least comparable (Linares et al 2014a), with some studies undertaken in the UK and Australia even indicating that cold-related deaths are of an order of magnitude greater than those related to heat . This lower degree of attention may perhaps be due to the fact that its influence on mortality is less pronounced and longer term (Alberdi et al 1998) and that there are other concomitant infectious winter factors (Healy 2003), though these do not wholly account for high winter respiratorycause mortality (Ebi and Mills 2013).…”
Section: Introductionmentioning
confidence: 97%